A technique for inferring zonal irregularity drift from single‐station GNSS measurements of intensity (S4) and phase (σφ) scintillations. Issue 8 (4th August 2016) - Carrano, Charles S.; Groves, Keith M.; Rino, Charles L.; Doherty, Patricia H.
Abstract: The zonal drift of ionospheric irregularities at low latitudes is most commonly measured by cross‐correlating observations of a scintillating satellite signal made with a pair of closely spaced antennas. The Air Force Research Laboratory–Scintillation Network Decision Aid (AFRL‐SCINDA) network operates a small number of very high frequency (VHF) spaced‐receiver systems at low latitudes for this purpose. A far greater number of Global Navigation Satellite System (GNSS) scintillation monitors are operated by the AFRL‐SCINDA network (25–30) and the Low‐Latitude Ionospheric Sensor Network (35–50), but the receivers are too widely separated from each other for cross‐correlation techniques to be effective. In this paper, we present an alternative approach that leverages the weak scatter scintillation theory to infer the zonal irregularity drift from single‐station GNSS measurements of S 4, σ φ, and the propagation geometry. Unlike the spaced‐receiver technique, this approach requires assumptions regarding the height of the scattering layer (which introduces a bias in the drift estimates) and the spectral index of the irregularities (which affects the spread of the drift estimates about the mean). Nevertheless, theory and experiment suggest that the ratio of σ φ to S 4 is less sensitive to these parameters than it is to the zonal drift. We validate the technique using VHF spaced‐receiver measurements of zonal irregularity drift obtained from the AFRL‐SCINDA network. While the spaced‐receiver technique remains the preferred way to monitor the drift when closely spaced antenna pairs are available, our technique provides a new opportunity to monitor zonal irregularity drift using regional or global networks of widely separated GNSS scintillation monitors. Key Points: We infer zonal irregularity drift from single‐station GNSS measurements of S4 and sigma‐phi Geometric control of scintillation differs between satellites, but inferred zonal drift does not GNSS‐estimated zonal drift compares favorably with VHF spaced‐receiver measurements